Legal and economic assessment of Neuralink: Between today's challenges and future aspirations analytical descriptive study - Azab, Rania S.; Ismail, Hosameldin H. (Edelweiss Applied Science and Technology, 2024)
This research explores the legal and economic challenges associated with Neuralink’s innovative technology that merges artificial intelligence with the human brain. This technology allows individuals to control devices with their thoughts and addresses neurological disorders, thereby enhancing human capabilities. Legal concerns focus on privacy issues arising from brain data collection, necessitating new laws to protect individual rights. Questions of liability for damages also arise, determining whether responsibility lies with Neuralink or the users. Additionally, the ethical implications of enhancing human abilities and their effects on identity are examined. Economically, Neuralink could drive innovation, increase productivity, and create specialized jobs while transforming the labor market. It holds promise for improving healthcare and education, thus enhancing overall quality of life. It highlights that protecting rights is vital for innovation and meeting societal needs. It emphasizes safeguarding individual rights to promote innovation and ensure technology benefits society.